Self-Referential Processing, Rumination, and Cortical Midline Structures in Major Depression - Nejad, Ayna B.; Fossati, Philippe; Lemogne, Cédric (Frontiers in Human Neuroscience, 2013)
Major depression is associated with a bias towards negative emotional processing and increased self-focus, i.e. the process by which one engages in self-referential processing. The increased self-focus in depression is suggested to be of a persistent, repetitive and self-critical nature and is conceptualised as ruminative brooding. The role of the medial prefrontal cortex in self-referential processing has been previously emphasised in acute major depression. There is increasing evidence that self-referential processing as well as the cortical midline structures play a major role in the development, course and treatment response of major depressive disorder. However, the links between self-referential processing, rumination, and the cortical midline structures in depression are still poorly understood. Here, we reviewed brain imaging studies in depressed patients and healthy subjects that have examined these links. The literature suggests that self-referential processing in major depression is associated with increased activity of the anterior cortical midline structures. Abnormal interactions between the lateralised task-positive network, and the midline cortical structures of the default mode network, as well as the emotional response network, may underlie the pervasiveness of ruminative brooding. Furthermore, targeting this maladaptive form of rumination and its underlying neural correlates may be key for effective treatment.